Experiences of a New Digital Economy in Brazilian Journalism: Strategy of Collaborative Interaction in Agência Pública’s crowdfunding - Gadini, Sérgio Luiz; Ortiz de Camargo, Isadora (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
Digital information provided easy access to many different scenarios and types of knowledge, besides strengthe-ning of media that survives independently managed, where technologies leverage the collective professional experience and techniques with funding from ‘new tools’ and society connected , as is the case of crowdfunding. This perspective of journa-lism that involves collaborative and financial participation of people, the brazilian case of ‘Agência Pública’ uses crowdfun-ding to promote investigative reporting and is the first project to use this strategy in Brazil. This paper relates the project with histories situations about associativism.